Membrane biophysics : as viewed from experimental bilayer lipid membranes (planar lipid bilayers and spherical liposomes) - Tien, H. Ti.; Ottova-Leitmannova, Angelica; ScienceDirect eBooks (Amsterdam ; New York : Elsevier, 2000)
This book summarizes the current status of research on bilayer lipid membranes (planar lipid bilayers and spherical liposomes). In addition to describing the properties of lipid bilayers and examining biomembrane phenomena, the book has two other objectives. The first is to present practical methods for the formation and study of lipid bilayers with either aqueous or metal-lipid bilayer interfaces. The second aim is to treat planar lipid bilayers as a new type of interfacial adsorption phenomena.
Cover -- Table of Contents -- Preface -- Chapter 1. Membrane Biophysics as Viewed from Experimental Bilayer Lipid Membranes (Planar BLMs and Liposomes) -- Chapter 2. Fundamental Aspects of Biological Membranes -- Chapter 3. Membrane Biophysics-Basic Principles -- Chapter 4. Experimental Models of Biomembranes -- Chapter 5. Membrane Transport -- Chapter 6. Membrane Electrochemistry -- Chapter 7. Membrane Physiology -- Chapter 8. Membrane Bioenergetics -- Chapter 9. Membrane Photobiophysics and Photobiology -- Chapter 10. Applications -- Index.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Biophysics; Lipid Bilayers; Biological Transport -- physiology; Biophysics; Cell Membrane -- physiology; Liposomes; Models, Biological; Transport biologique; Membranes (Biologie); Membranes lipidiques bimoléculaires.; Biophysique; SCIENCE -- Life Sciences -- Cell Biology; Biophysics; Electronic books